Preoperative and Postoperative Opioid Dependence in Patients Undergoing Anterior Cervical Diskectomy and Fusion for Degenerative Spinal Disorders - Dietz, Nicholas; Sharma, Mayur; Alhourani, Ahmad; Ugiliweneza, Beatrice; Nuno, Miriam; Drazin, Doniel; Wang, Dengzhi; Boakye, Maxwell (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Anterior cervical diskectomy and fusion (ACDF) is a procedure for effectively relieving radiculopathy. Opioids are commonly overprescribed in postsurgical settings and prescriptions vary widely among providers. We identify trends in opioid dependence before and after ACDF.Methods We used the Truven Health MarketScan data to identify adult patients undergoing ACDF for degenerative cervical spine conditions between 2009 and 2015. Patients were segregated in four cohorts of preoperative and postoperative opioid nondependence (ND) or dependence (D) with 15 months of postoperative follow-up.Results A total of 25,403 patients with median age of 52 years (18–92) who underwent ACDF met the inclusion criteria. Breakdown of the four cohorts was as follows: prior nondependent who remain nondependent (NDND): 62.76% (n = 15,944); prior nondependent who become dependent (NDD): 4.6% (n = 1,168); prior dependent who become nondependent (DND): 14.03% (n = 3,564); and prior dependent who remain dependent (DD): 18.61% (n = 4,727). Opioid dependence decreased 9.43% postoperatively. Overall payments and 30-day readmissions increased 1.96 and 1.79 times for opioid dependent versus nondependent cohorts, respectively. Adjusted payments at 3 to 15 months were significantly increased for dependent cohorts with 3.56-fold increase for the DD cohort when compared with the NDND cohort. Length of stay, complications, medication refills, outpatient measures, and hospital admissions were also higher in those groups with postoperative opioid dependence when compared with those who were not opioid dependent.Conclusions Opioid dependence after ACDF is associated with increased hospital readmissions, complication rates at 30 days, and payments within 3 months and 3 to 15 months postdischarge. Overall opioid dependence was decreased after ACDF procedure, however, a smaller number of opioid-dependent and opioid-naive patients became dependent postoperatively and should be followed carefully.
Keywords: ACDF; opioids; opioid dependence; analgesia; spine surgery